Indirect Band Gap in Scrolled MoS2 Monolayers - Na, Jeonghyeon; Park, Changyeon; Lee, Chang Hoi; Choi, Won Ryeol; Choi, Sooho; Lee, Jae Ung; Yang, Woochul; Cheong, Hyeonsik; Campbell, Eleanor E.B.; Jhang, Sung Ho (Nanomaterials, 2022)
MoS2 nanoscrolls that have inner core radii of ∼250 nm are generated from MoS2 monolayers, and the optical and transport band gaps of the nanoscrolls are investigated. Photoluminescence spectroscopy reveals that a MoS2 monolayer, originally a direct gap semiconductor (∼1.85 eV (optical)), changes into an indirect gap semiconductor (∼1.6 eV) upon scrolling. The size of the indirect gap for the MoS2 nanoscroll is larger than that of a MoS2 bilayer (∼1.54 eV), implying a weaker interlayer interaction between concentric layers of the MoS2 nanoscroll compared to Bernal-stacked MoS2 few-layers. Transport measurements on MoS2 nanoscrolls incorporated into ambipolar ionic-liquid-gated transistors yielded a band gap of ∼1.9 eV. The difference between the transport and optical gaps indicates an exciton binding energy of 0.3 eV for the MoS2 nanoscrolls. The rolling up of 2D atomic layers into nanoscrolls introduces a new type of quasi-1D nanostructure and provides another way to modify the band gap of 2D materials.
Keywords: 1D structure; band gap; ionic liquid gating; MoS2; rolled structure; scrolled MoS2